2021
DOI: 10.1186/s12935-021-01792-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a prognostic and therapeutic immune signature associated with hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most prevalent and inflammation-associated cancers. The tumor microenvironment (TME) plays an essential role in HCC development and metastasis, leading to poor prognosis. The overall TME immune cells infiltration characterizations mediated by immune-related genes (IRGs) remain unclear. In this study, we aimed to investigate whether immune-related genes could be indicators for the prognosis of HCC patients and TME cell infiltration charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 68 publications
4
53
0
Order By: Relevance
“…Unfortunately, however, few clinical studies have revealed the role of TMB in HCC. We and others found a significant correlation between TMB and immune infiltration in HCC ( 5 7 ). Most importantly, the PS model was significantly associated with TMB and immune infiltration.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Unfortunately, however, few clinical studies have revealed the role of TMB in HCC. We and others found a significant correlation between TMB and immune infiltration in HCC ( 5 7 ). Most importantly, the PS model was significantly associated with TMB and immune infiltration.…”
Section: Discussionsupporting
confidence: 63%
“…A detailed understanding of the mechanism underlying immune infiltration may favor precision immunotherapy in HCC. Tumor mutation burden (TMB) refers to the total number of mutations in the coding region of the evaluated gene in the tumor cell (TC) genome, which is calculated by the total number of mutations per megabase in the genome (5)(6)(7). Previous reports suggested the close association of TMB with immune infiltration, while the molecular mechanism remains inconclusive (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…We reason that the poorer prognosis of patients with PAAD in the high-risk subgroup could be attributed to the enhanced expression of immune checkpoints. It has been well established that higher expression of immune checkpoint molecules usually benefits more from immune checkpoint inhibitors (ICIs; Peng et al, 2021 ). Overall, these data indicate that patients with PAAD in the high-risk subgroup might have improved prognoses through the application of ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a five-gene immune-related signature ( LDHA , PPAT , BFSP1 , NR0B1 , and PFKFB4 ) was identified and used to establish a prognostic model for responses to HCC treatment that could stratify patients who were sensitive to immunotherapy ( 93 ). Other studies using different gene combination strategies have also reported their potential to predict ICI responses by reflecting the characteristics of the immune microenvironment ( 94 , 95 ). Nevertheless, these signatures need further testing for clinical application.…”
Section: Potential Predictive Biomarkers For Ici-based Treatmentmentioning
confidence: 99%